2021
DOI: 10.2147/ott.s283459
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Mesenchymal Stem Cells-Derived Extracellular Vesicles Promote Proliferation, Invasion and Migration of Osteosarcoma Cells via the lncRNA MALAT1/miR-143/NRSN2/Wnt/β-Catenin Axis

Abstract: Introduction Osteosarcoma is a malignant primary bone tumor. Bone marrow-derived mesenchymal stem cells-derived extracellular vesicles (BMSC-EVs) bear repair function for bone and cartilage. This study investigated the mechanism of BMSC-EVs in osteosarcoma cell proliferation, migration and invasion. Methods BMSC-EVs were isolated and identified. The effects of different concentrations of EVs on osteosarcoma cell proliferation, migration and invasion were evaluated. LncR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 37 publications
0
28
0
Order By: Relevance
“…BMSCs, the OS precursor cells, participate in OS progression through cell-to-cell interactions [ 20 ]. BMSC exosomes play important roles in this process, but the specific mechanism remains unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BMSCs, the OS precursor cells, participate in OS progression through cell-to-cell interactions [ 20 ]. BMSC exosomes play important roles in this process, but the specific mechanism remains unclear.…”
Section: Resultsmentioning
confidence: 99%
“…BMSCs promote the development of breast cancer and prostate cancer [ 17 ], yet inhibit the progression of glioblastoma and hepatocellular carcinoma [ 18 , 19 ]. Moreover, OS cells may originate from BMSCs, while BMSCs regulate OS metastasis [ 20 ]. However, the mechanism by which BMSCs regulate the malignant progression of OS remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Caution must be practised however, as the protection afforded to other cells by MSCs and their EVs can have a negative effect in cancer. For example, Li and colleagues showed that EVs from bone marrow-derived MSCs can enhance osteosarcoma cell proliferation, invasion and migration in a mechanism involving the Wnt-B-catenin signaling [215]. Furthermore, Guo and colleagues showed that MSC-derived EVs containing miR-130b-3p promotes the progression of lung cancer [216].…”
Section: Mesenchymal Stem Cell-derived Extracellular Vesiclesmentioning
confidence: 99%
“…Electron microscopic examination revealed the presence of EVs of 50-200 nm in diameter that derive from bone and tumor cells. MSC-derived exosomes can promote cell proliferation, migration and invasion in osteosarcoma in vitro and in vivo [78,79]. Moreover, MSC-EVs can also promote autophagy contributing to MSC-EV-induced promotion of malignant tumorigenesis [78].…”
Section: Role Of Evs In Osteosarcoma Microenvironment and Tumoral Growthmentioning
confidence: 99%